2018
DOI: 10.1159/000487143
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Regulation of Ewing Sarcoma Cell Function

Abstract: Objective: Ewing sarcoma (ES) is a type of childhood cancer probably arising from stem mesenchymal or neural crest cells. The epidermal growth factor receptor (EGFR) acts as a driver oncogene in many types of solid tumors. However, its involvement in ES remains poorly understood. Methods: Human SK-ES-1 and RD-ES ES cells were treated with EGF, the EGFR inhibitor tyrphostin (AG1478), or phosphoinositide 3-kinase (PI3K) or extracellular-regulated kinase (ERK)/mitogen-activated kinase (MAPK) inhibitors. Cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…40 Herein, we also found that combined TAE226 and conventional chemotherapeutic (vincristine, doxorubicin, and etoposide) treatment had synergistic effects against EWS. Recently, other candidate EWS inhibitors, such as EGFR and Trk inhibitors, 43,44 have been reported to be potential future therapeutic agents. A combination therapy of these drugs in addition to conventional chemotherapy and TAE226 treatment may improve the prognosis of patients with EWS.…”
Section: Discussionmentioning
confidence: 99%
“…40 Herein, we also found that combined TAE226 and conventional chemotherapeutic (vincristine, doxorubicin, and etoposide) treatment had synergistic effects against EWS. Recently, other candidate EWS inhibitors, such as EGFR and Trk inhibitors, 43,44 have been reported to be potential future therapeutic agents. A combination therapy of these drugs in addition to conventional chemotherapy and TAE226 treatment may improve the prognosis of patients with EWS.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, B7-H3-based CARs are now in phase I clinical trials in pediatric solid tumors including EWS (NCT04897321, NCT04483778). Finally, the epithelial growth factor receptor (EGFR) is another target for CAR therapy in EWS and its inhibition has an antitumor activity in vitro [ 101 ]. A phase I trial using EGFR-CAR (EGFR806) is recruiting relapsed patients with preliminary data indicating acceptable toxicity and antitumor activity in children and young adults (NCT03618381) [ 102 ].…”
Section: Epigenetic and Immunotherapy-based Treatments In Ews: Moving...mentioning
confidence: 99%
“…It is involved in routine cellular processes such as proliferation, differentiation, and cellular development [83]. EGFR is highly expressed in several solid cancers [84]. EGFR is overexpressed in up to 76% of embryonal RMS cases, so it is considered a suitable target for RMS immunotherapy [85].…”
Section: Immunotoxins For Sarcomamentioning
confidence: 99%